Resection of isolated local and metastatic recurrence in periampullary adenocarcinoma. Issue 3 (22nd April 2013) - Boone, Brian A.; Zeh, Herbert J.; Mock, Brady K.; Johnson, Paul J.; Dvorchik, Igor; Lee, Ken; Moser, A. James; Bartlett, David L.; Marsh, J. Wallis
Abstract Background The majority of patients with periampullary cancer develop local or metastatic recurrence despite successful negative margin resection. Unfortunately, there are no established therapeutic strategies for managing these patients. The literature on the surgical resection of recurrent disease is limited. Methods This is a retrospective study evaluating patients who underwent reoperative resection of recurrent periampullary cancer at a single institution between 1990 and 2011. Perioperative outcomes were compared with those of the original primary resections for patients with local recurrence. Kaplan–Meier curves were used to evaluate survival. Results Twenty‐two patients underwent reoperative resection following the successful primary resection of periampullary cancers. Median survival from the time of reoperation was 28.1 months. A greater survival benefit was seen in patients undergoing reoperative resection with >15 months between the primary resection and recurrence (40.6 months versus 8.2 months; P < 0.05). Complication rates were lower after reoperative resection compared with the primary resection (20% versus 70%). Perioperative characteristics including operative time, estimated blood loss and hospital stay were similar in both the primary and reoperation procedures. Conclusions Surgical resection of periampullary cancer recurrence is feasible, safe and may offer survival benefits in comparison with alternative treatment modalities. Reoperative resection should be considered, especially in patients in whom the time to recurrence is lengthy.